SAT-410 Long Term Evaluation of TSH Receptor Antibodies and Thyroid Stimulating Immunoglobulin After Radioiodine Therapy for Thyrotoxicosis - Marui, Suemi (J Endocr Soc, 2020)
Background Radioioactive iodine therapy (RAI) is an excellent choice to treat thyrotoxicosis, particularly Graves′ disease (GD) patients. After RAI therapy, it is well known that TSH receptor antibodies (TRAb) rise in GD patients and autoimmunity can eventually surge in patients with toxic multinodular or uninodular goiter (TNG). Recently, biological assay distinguishes stimulating TRAb, called thyroid stimulating immunoglobulin (TSI) bringing a new perspective on follow-up, as TSI is involved in Graves′ pathogenesis of persistent thyrotoxicosis and ophthalmopathy after RAI therapy. Objective Analyze TRAb and TSI levels after 6 and 12 months of RAI therapy for thyrotoxicosis. Patients and Methods Patients were evaluated prospectively immediately before and 6 to 12 months after RAI therapy for thyrotoxicosis. Thyroid hormones were all measured using immunoassays (Roche Diagnostics Ltd). TRAb was analyzed by Elecsys Anti-TSHR assay (Roche Diagnostics, Germany) and was considered negative if < 1.75 IU/L (analytical range: 0.3 to 40 IU/L). TSI was measured by Immulite TSI assay (Siemens Healthcare, UK) and was considered negative if < 0.55 IU/L (analytical range: 0.1 to 40 IU/L). Clinical data and comparison of assays were analyzed by SPSS and MedCalc softwares. Results From 2017 to 2019, 54 patients (44 females) were prospectively evaluated after 6 months of RAI therapy, mostly because of GD (40 patients). A high degree correlation was observed between TRAb and TSI (Spearman correlation coefficient =0.875; p < 0.0001, 95% CI 0.784 to 0.929). After 6 months, among patients with GD, 5/40 patients had negative TRAb levels and 2/40 had negative TSI levels, whereas all TNG patients had both negative TRAb and TSI levels. In GD group, 4 patients showed subclinical hyperthyroidism and relapse occurred in 1 case. All patients with TNG showed euthyroidism status with or without thyroid medications. One year after RAI therapy, we evaluated 32 patients (23 GD) and 4/23 of GD had negative TRAb levels and only 1/23 had negative TSI level. All patients with TNG had negative TRAb and TSI levels after one year fo treatment. Subclinical hyperthyroidism was diagnosed in 5 patients with GD but none with TNG. Along follow-up, 4 patients with clinical diagnosis of GD with TRAb negative before RAI therapy became positive after RAI therapy and 3 patients became TSI positive. Conclusions Long term after RAI therapy for thyrotoxicosis treatment, TRAb and TSI are still positive in most GD patients and few cases can even turned to positive levels. Nevertheless, in TNG patients, RAI therapy is safe as TRAb and TSI maintained at negative concentrations and thyrotoxicosis is properly resolved.